Factors Influencing Professional Skills Among Accounting Students at KwaZulu-Natal Universities. - NOMLALA, Bomi Cyril; MVUNABANDI, Jean Damascene (International Journal of Environmental, Sustainability, and Social Science, 2023)
Employers are increasingly expressing concern that the majority of recent graduates lack professional skills. In addition, it is unknown whether students pursuing accounting degrees in professionally accredited institutions are more financially savvy than those in non-accredited institutions. 1582 undergraduate accounting students at the University of KwaZulu-Natal (UKZN), Mangosuthu University of Technology (MUT), and Durban University of Technology (DUT) were surveyed using self-administered questionnaires. The data was analysed using Statistical Package for the Social Sciences version 25 (SPSS 25). The results indicated that the majority of respondents were female. 72.6 percent of respondents are influenced by South African Institute of Charted Accountants (SAICA) accreditation, whereas 95.2 percent of respondents with outstanding professional skills are influenced by non-SAICA accreditation. The study's findings disprove previous claims that accreditation has no bearing on students' abilities. Finally, the investigation contributes South Africa-relevant knowledge..